THE ROLE OF MONETARY POLICY IN THE ECONOMY (Web of Technology: Multidimensional Research Journal, 2024)
This article indicates the monetary policy, and examines the scientific and theoretical views of foreign economists in this regard. Also, the influence of monetary policy instruments on the supply and demand of money in the economy is analyzed. In particular, the change in the refinancing rate on the growth rate of monetary aggregates in Uzbekistan. Scientific, practical proposals and recommendations have been developed to increase the role of monetary policy in Uzbekistan.